Pancasila as an Entity and Identity in 21st Century Education and Efforts to Strengthen the Profile of Pancasila Students - Asri Arumsari (Education Specialist, 2023)
This study aims to identify and describe Pancasila as an entity and identity in 21st century education as an effort to strengthen the profile of Pancasila students. In this study using a librarian study approach that examines and discusses literature review from various sources both from books, journals and relevant previous research and qualitative methods to describe or describe this research. The results of the research show that Pancasila is in his life as a citizen. learning development should use a student-centered learning approach. Students are placed as learning subjects who actively develop their interests and potential. So the independent curriculum was developed as a curriculum framework that is more flexible, while also focusing on essential material and developing the character and competence of students. Pancasila students are the embodiment of Indonesian students as lifelong students who have global competence and behave in accordance with Pancasila values, with six main characteristics: faith, fear of God Almighty, and noble character, global diversity, mutual cooperation, independence, critical reasoning, and creative.